Skin care education and individual counselling versus treatment as usual in healthcare workers with hand eczema: randomised clinical trial - Ibler, Kristina S.; Diepgen, Thomas L. (The BMJ, 2012)
Objective To evaluate the effect of a secondary prevention programme with education on skin care and individual counselling versus treatment as usual in healthcare workers with hand eczema. Design Randomised, observer blinded parallel group superiority clinical trial. Setting Three hospitals in Denmark. Participants 255 healthcare workers with self reported hand eczema within the past year randomised centrally and stratified by profession, severity of eczema, and hospital. 123 were allocated to the intervention group and 132 to the control group. Interventions Education in skin care and individual counselling based on patch and prick testing and assessment of work and domestic related exposures. The control was treatment as usual. Main outcome measures The primary outcome was clinical severity of disease at five month follow-up measured by scores on the hand eczema severity index. The secondary outcomes were scores on the dermatology life quality index, self evaluated severity of hand eczema, skin protective behaviours, and knowledge of hand eczema from onset to follow-up. Results Follow-up data were available for 247 of 255 participants (97%). At follow-up, the mean score on the hand eczema severity index was significantly lower (improved) in the intervention group than control group: difference of means, unadjusted −3.56 (95% confidence interval −4.92 to −2.14); adjusted −3.47 (−4.80 to −2.14), both P=0.001 for difference. The mean score on the dermatology life quality index was also significantly lower (improved) in the intervention group at follow-up: difference of means: unadjusted −0.78, non-parametric test P=0.003; adjusted −0.92, −1.48 to −0.37). Self evaluated severity and skin protective behaviour by hand washings and wearing of protective gloves were also statistically significantly better in the intervention group, whereas this was not the case for knowledge of hand eczema. Conclusion A secondary prevention programme for hand eczema improved severity and quality of life and had a positive effect on self evaluated severity and skin protective behaviour by hand washings and wearing of protective gloves. Trial registration ClinicalTrials.gov NCT01012453.
Gesehen am 19.11.2018